The relationship between human resources management and turnover intention among generation Y employees in Malaysia - Tanwa, Owodunni Oluwakemi (Management Centre,International Islamic University Malaysia, 2014)
This study examines the relationship between human resource (HR) management practices and turnover intention among generation Y employees in Malaysia. The HR management practices studied include training and development (T &D), compensation and performance appraisal (PA). Turnover intention among Gen Y has been found to be increasing over time. The study used primary data by conducting a survey on Gen Y employees in Malaysia especially in Klang Valley area. A sample of one hundred and ninety-nine (199) Gen Y employees was drawn using purposive sampling techniques. Pearson Correlation Coefficient was used to determine the relationship between Gen Y turnover intention and all the three HRM practices. The implication of this study gives some insights to the HR managers on the specific HRM practices or strategies that can be used to cater for Gen Y in employees, which will subsequently reduce the turnover intention.